Prospects for improvement in the design of residential buildings in Jeddah integrating passive ventilation systems and enhanced family interaction - Krimly, Salah (2020)
Background: This thesis proposes that in order to provide house residents with an environmentally, socially, and culturally sustainable dwelling, three key factors must be considered together: the architectural design, the family social life within the house and the environmental technologies and systems employed to maintain thermal comfort. Currently, the majority of the existing literature focuses on linking only two of these three research areas, therefore there is a lack of existing research linking these three areas.